Pengaruh Pemberian Tiamin Intravena terhadap Kadar Tumor Necrosis Factor Alpha (TNF- α) pada Pasien COVID-19 di Ruang Isolasi - Lubis, Andriamuri Primaputra; Annisa Syifanurhati; Muhammad Ihsan (Majalah Anestesia & Critical Care, 2022)
Introduction : Many cytokines and inflammatory mediators play a role in the progression of COVID-19 disease, including the interleukins, interferons, and tumor necrosis factor-α (TNF-α.) groups. An intervention is needed to reduce the levels of this cytokine. Thiamine has the potential to reduce levels of proinflammatory cytokines, especially TNF-α. Objective: To determine the effect of intravenous thiamine administration on TNF-α levels in COVID-19 patients in the isolation room of RSUP H Adam Malik. Methods: This study used an analytical design of one group pre test - post test in the isolation room of Haji Adam Malik General Hospital Medan with a sample size of 16 people. Samples were given thiamine IV 200 mg/12 hours and then the levels of TNF-α were measured by ELISA method. Results: Characteristics of the sample obtained were equal in number of males and females (1:1), the mean age was 43 ±14.78 years, the mean BMI was 23.31 ± 6.55, the mean systolic was 122.50 ± 5.77 mmHg and diastolic 88.88 ± 6.55 mmHg. The majority of the sample (50%) had no comorbidities. Before administration of thiamine, the median TNF-α was 186.5 pg/mL with a minimum and maximum value (171-420 pg/mL) and after administration of thiamine, the median TNF-α was 180.50 pg/mL with a minimum and maximum value (122-200 pg/mL) obtained a p value of 0.001 < 0.05 (there is a significant effect). Conclusion: In this study, the mean TNF-α level was lower when given intravenous thiamine. This decrease in TNF-α levels was also found to be significant after intravenous thiamine administration.